HEAT WAVE AND ITS IMPACT IN NORTHEASTERN NIGERIA: A CASE STUDY OF YOBE STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
Heatwaves are significant natural disaster that is caused primarily by extreme temperatures. The extreme heat events associated with heatwaves often cause severe health complications and deaths. In view of the environmental hazards associated with heatwaves, this study investigated the impact of heatwaves in Yobe State, northeast Nigeria. Temperature and humidity data of thirty years (1991-2020) for the hot season (March-June), were obtained from the Nigerian Meteorological Agency (NiMet) Abuja.  Time series analysis and basic statistical tools were used to analysis the data which was used to evaluate the trend of heatwaves and their impact in the study area. The results of the study showed that 2010 was extremely hot with an average maximum temperature anomaly of 2.18, while 2013 and 2015 have an average maximum temperature anomaly of 1.93 respectively, and were very hot. The trend in the average maximum temperature anomaly of the study area showed a continuous increase in extreme heat for about a decade (2009-2020). The positive temperature trend and the average maximum temperature anomaly showed that the intensity of heatwaves in the study area will increase in the future as a result of global warming caused by the continuous emission of anthropogenic greenhouse gases. The results also showed that the heatwaves were exacerbated by the drought which occurred between 2010 and 2014.  The annual heat index which range from 29.4oC - 34oC in the study area showed that the heatwaves have impacted both human and animals negatively in the area.
Keywords: Heatwave, Temperature, Anomaly, Heat-index, Global warming.